OPTIMALISASI E-COMMERCE MELALUI TEKNOLOGI WEB MODERN - Asnia Ramadhani; Melni Melni; Nurkhafitri Sahra; Alya Nabila; Dhimas Tribuana (Plexi Digital Indonesia, 2025)
This research aims to identify adoption trends, key benefits, and challenges in e-commerce optimization using modern web technologies such as Next.js, Laravel, Headless/Decoupled architecture, and Progressive Web Applications (PWA). The method used is a Systematic Literature Review (SLR) of academic publications from 2020 to 2025, with a comprehensive search across various scientific databases. The main results show a significant shift towards Headless/Decoupled Commerce, where Next.js is the dominant frontend framework and Laravel is the preferred backend. The implementation of these technologies consistently improves Core Web Vitals scores, data delivery efficiency, and SEO indexing, as well as increasing user engagement and retention on mobile through PWAs. Nevertheless, the challenges faced include initial development complexity, third-party integration, and a steep learning curve. In conclusion, the adoption of Headless Commerce with Next.js and PWA is an essential strategy to achieve competitive advantage in e-commerce business metrics.